Jankyn's Book of Wikked Wyves : Seven Commentaries on Walter Map's "Dissuasio Valerii" - Map, Walter, active 1200; Hanna, Ralph (Book collections on Project MUSE., 2014)
In volume 1 of Jankyn's Book of Wikked Wyves (Georgia, 1997), Ralph Hanna and Traugott Lawler presented authoritative versions of three medieval texts invoked by Jankyn (fifth husband of the Wife of Bath) in The Canterbury Tales . In Jankyn's Book, volume 2, Lawler and Hanna revisit one of those texts by way of presenting all the known contemporary commentaries on it. The text is Walter Map's ""Dissuasio Valerii, "" that is, ""The Letter of Valerius to His Friend Ruffinus, Dissuading Him from Marrying."" Included in Jankyn's Book, volume 2, are seven commentaries on ""Dissuasio Valerii, "" edit.